Heterocyclic tautomerism: reassignment of two crystal structures of 2‐amino‐1, 3‐thiazolidin‐4‐one derivatives. Issue 8 (15th August 2014) - Gzella, Andrzej K.; Kowiel, Marcin; Suseł, Aneta; Wojtyra, Magdalena N.; Lesyk, Roman
<x xml:space="preserve">Abstract</x> The structures of 5‐(2‐hydroxyethyl)‐2‐[(pyridin‐2‐yl)amino]‐1, 3‐thiazolidin‐4‐one, C10H11N3O2S, (I), and ethyl 4‐[(4‐oxo‐1, 3‐thiazolidin‐2‐yl)amino]benzoate, C12H12N2O3S, (II), which are identical to the entries with refcodes GACXOZ [Váňa et al. (2009). J. Heterocycl. Chem.46, 635–639] and HEGLUC [Behbehani & Ibrahim (2012). Molecules, 17, 6362–6385], respectively, in the Cambridge Structural Database [Allen (2002). Acta Cryst. B58, 380–388], have been redetermined at 130 K. This structural study shows that both investigated compounds exist in their crystal structures as the tautomer with the carbonyl–imine group in the five‐membered heterocyclic ring and an exocyclic amine N atom, rather than the previously reported tautomer with a secondary amide group and an exocyclic imine N atom. The physicochemical and spectroscopic data of the two investigated compounds are the same as those of GACXOZ and HEGLUC, respectively. In the thiazolidin‐4‐one system of (I), the S and chiral C atoms, along with the hydroxyethyl group, are disordered. The thiazolidin‐4‐one fragment takes up two alternative locations in the crystal structure, which allows the molecule to adopt R and S configurations. The occupancy factors of the disordered atoms are 0.883 (2) (for the R configuration) and 0.117 (2) (for the S configuration). In (I), the main factor that determines the crystal packing is a system of hydrogen bonds, involving both strong N—H...N and O—H...O and weak C—H...O hydrogen bonds, linking the molecules into a three‐dimensional hydrogen‐bond network. On the other hand, in (II), the molecules are linked via N—H...O hydrogen bonds into chains.